Shear bond strength of orthodontic brackets on enamel surface conditioned by biolase er YSGG laser - Ataee, Kiarash Mehdipoor
Introduction. The objectives of this study were to: 1) compare the shear bond strength (SBS) of brackets bonded to enamel, conditioned by Biolase Er:YSGG Laser and to acid-etched enamel; 2) compare the etching patterns on enamel produced by Biolase Er:YSGG laser conditioning and acid etchant, 3) to evaluate the differences in Adhesive Remnant Index between the laser conditioned and acid-etched groups.